Evaluation of hypertension knowledge and its association with medication adherence among hypertensive patients attending primary health centers: a cross-sectional study from eastern Saudi Arabia - Al-Hazmi, Ahmad Homoud; Alanazi, Abdullah Dhoimi Mureed; Thirunavukkarasu, Ashokkumar; Alriwely, Nasser Saleh; Alrais, Mmdoh Mohammad F.; Alruwaili, Alreem Barghash S.; Alnosairi, Mona Saleh; Alsirhani, Amnah Ibrahim (Frontiers in Public Health, 2025)
Background and aimThe global healthcare system acknowledged the crucial role of disease knowledge in health outcomes and improving quality of life among patients with chronic disease. A lack of adequate knowledge and understanding of hypertension, its symptoms, and available treatments can lead to poor treatment outcomes. The present study aimed to determine the level of hypertension knowledge and associated factors among hypertensive patients. Furthermore, we evaluated the correlation between levels of knowledge and medication adherence among them.MethodsThe present study was carried out among 406 hypertensive patients attending different primary health centers in Hafr Al Batin, Saudi Arabia. Participants’ hypertension-related knowledge was evaluated using the validated hypertension knowledge–level scale, and adherence practice was evaluated using the medication adherence and refill scale. We categorized the knowledge score into low, medium, and high, according to Bloom’s criteria. We applied Spearman’s correlation test to find the strength and direction of the correlation between hypertension-related knowledge and medication adherence. Furthermore, we used binomial logistic regression analysis to find the associated factors of the low hypertension-related knowledge among the patients.ResultsOf the studied patients, only 10.3% demonstrated a high level of knowledge, and the highest knowledge levels were observed in the domains of complications (x¯ = 4.39, standard deviation [SD] = 1.20) and lifestyle (x¯ = 3.13, SD = 0.69), while knowledge about drug compliance (x¯ = 0.62, SD = 0.98) was the lowest. A statistically significant positive correlation was observed between knowledge and adherence regarding hypertension (rho = 0.268, p = 0.001) among study participants. We observed that marital status (p = 0.032), income (p = 0.042), and absence of chronic diseases (p = 0.001) are associated factors for low hypertension-related knowledge.ConclusionThe study findings highlight a moderate level of knowledge about hypertension among patients, with significant gaps in drug compliance understanding. The positive correlation between knowledge and medication adherence underscores the need for better hypertension education at primary health centers. Furthermore, it is recommended that future prospective studies be conducted within various cultural contexts.